Pemodelan Kasus Pasien Terkonfirmasi Positif Covid-19 Per-Hari Di Indonesia dengan Metode SARIMA - Wigid Hariadi; Sulantari Sulantari (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2021)
The Seasonal Autoregressive Integrated Moving Average (SARIMA) model is a popular method for forecasting univariate time series data for data containing seasonality. This method consists of several stages, namely: identification, parameter assessment, diagnostic examination, and forecasting using the SARIMA (p,d,q)(P,D,Q)S model. The SARIMA model can be applied in various fields, one of which is the medical field. The number of patients infected with the CoVID-19 virus continues to grow every day. Indonesia is one of the countries experiencing the impact of the COVID-19 virus. On December 28, 2021, the number of positive Covid-19 patients in Indonesia was 4,262,157, with 4,113,472 patients recovering and 144,071 patients dying. Seeing the high number of positive cases of Covid-19 in Indonesia, the author wants to conduct research on modeling cases of patients who are confirmed to be positive for Covid-19 per day in Indonesia and then from this model, data forecasting will be carried out for the next 28 periods. The data collection period is from November 1, 2021 to December 28, 2021. And the results of a good model for predicting cases of confirmed positive COVID-19 patients per day in Indonesia are the SARIMA (2,1,2)(2,1,1)7 model, with The seasonal length is 7 periods, and the sum squared resid is 0.927619. Abstrak Model Seasonal Autoregressive Integrated Moving Average (SARIMA) adalah metode populer untuk meramalkan data deret waktu univariat untuk data yang mengadung musiman. Metode ini terdiri dari beberapa tahapan, yaitu: identifikasi, penilaian parameter, pemeriksaan diagnostik, dan peramalan menggunakan model SARIMA (p,d,q)(P,D,Q)S. Model SARIMA dapat diterapkan di berbagai bidang, salah satunya bidang medis. Jumlah pasien yang terinfeksi virus CoVID-19 terus bertambah setiap harinya. Negara Indonesia merupakan salah satu Negara yang mengalami dampak virus covid-19. pada 28 Desember 2021, jumlah pasien positif Covid-19 di Indonesia sebanyak 4.262.157 pasien, dengan 4.113.472 pasien sembuh dan 144.071 pasien meninggal dunia. Melihat tingginya kasus positif Covid-19 di Indonesia, maka penulis ingin melakukan penelitian tentang pemodelan kasus pasien terkonfirmasi positif covid-19 perhari di Indonesia untuk kemudian dari model tersebut akan dilakuakn peramalan data untuk 28 periode kedepan. Periode pendataan dari tanggal 1 November 2021 sampai dengan 28 Desember 2021. Dan hasil model yang baik untuk memprediksi kasus pasien terkonfirmasi positif covid-19 perhari di Indonesia adalah model SARIMA (2,1,2)(2,1,1)7, dengan panjang musiman nya 7 periode, dan nilai sum squared resid sebesar 0.927619.